Safety and efficacy of topical insulin in ocular surface disorders: a systematic review and meta-analysis - Luís J. de Oliveira-Andrade; Gabriela C. Matos-de Oliveira; Alcina Ma. Vinhaes-Bittencourt; Tulio Matos-David; Roseanne Montargil-Rocha; Luís Matos-De Oliveira (Revista Mexicana de Endocrinología, Metabolismo y Nutrición, 2025)
Background: Ocular surface disorders (OSD) are prevalent, affecting millions globally. Existing treatments often have limitations, especially for severe cases. Objective: To evaluate the safety and efficacy of topical insulin for anaging OSDs. Methods: A comprehensive search of major databases (PubMed, Scopus, Embase, and Cochrane Library) identified studies investigating topical insulin for eye conditions. Rigorous screening and quality assessment were conducted. Data on safety, efficacy, and outcomes were extracted and analyzed. Results: Ten studies (1 case-control, 3 randomized prospective, 3 retrospective, and 3 double-blind) were included, exploring conditions like corneal ulcers, persistent defects, and dry eye disease. Findings suggest that topical insulin may be safe and effective for various OSD. A meta-analysis demonstrated significantly faster healing times with topical insulin compared to placebo. Conclusion: This review provides promising evidence for the therapeutic potential of topical insulin for diverse OSD. Despite limitations, topical insulin may be a viable treatment for OSD.